Role of Enterprise Resource Planning Systems in Achieving Competitive Priorities: The Egyptian International Pharmaceutical Industries Company "Epico" in Dakahlia governorate (Entrepreneurship Journal for Finance and Business, 2023)
This study investigates the effect of Enterprise Resource Planning Systems on achieving the Competitive Priorities. It also aims to determine the relationship between the Effectiveness of Enterprise Resource Planning Systems and achieving the Competitive Priorities. The researcher adopted the descriptive analytical approach and used a questionnaire as a primary tool for data collection. The study population consisted of (130) workers at the Egyptian International Pharmaceutical Industries Company "Epico" in Dakahlia governorate.This study revealed a significant effect for the Effectiveness of Enterprise Resource Planning Systems on achieving the Competitive Priorities (56%). There is a strong positive correlation relationship between Effectiveness of Enterprise Resource Planning Systems and achieving the Competitive Priorities (0.746). The study draws a set of recommendations the most important of which, First: Management's attention to improving the capabilities of users of enterprise resource planning systems. Second: To increase the awareness of the importance of the cost element. Third: To take care of customers' needs and expectations.